Evaluation of seat vibration sources in driving condition using spectral analysis - Mohammad Hosseini, Fouladi; Mohd. Jailani, Mohd. Nor; Othman, Inayatullah; Ahmad Kamal, Ariffin (Taylor's University, 2011)
Link to publisher's homepage at http://www.taylors.edu.my/